2018
DOI: 10.1016/j.juro.2018.02.2553
|View full text |Cite
|
Sign up to set email alerts
|

Mp78-05 Invasion-Associated Mirnas S as Possible Diagnostic Biomarkers of Muscle Invasive Bladder Cancer in Tumor Tissues and Urinary Exosomes

Abstract: myeloid-derived suppressor cells (MDSC) could be affected by chemotherapy and correlate with pathologic response in bladder cancer patients receiving neo-adjuvant chemotherapy.METHODS: Pretreatment Peripheral blood levels of granulocytic (G-MDSC) and monocytic MDSC (M-MDSC) were measured by fow cytometry. We divided patients into high and low (above and below the median, respectively) groups based on the median value for each immune cell subset and compared outcomes of the two groups.RESULTS: A signi?cant path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Urinary biomarkers could also be used to correctly identify MIBC patients that require radical cystectomy, a treatment that severely affects the quality of life. Although no such biomarkers have been identified to date, Baumgart et al identified three miRNAs (miR-30a-3p, miR-99a-5p, and miR-137-3p) that were upregulated and two (miR-141-3p and miR-205-5p) that were downregulated in exosomes secreted by invasive BCa cells versus those secreted by noninvasive BCa cells [ 84 ]. However, the suitability of these miRNAs as liquid biomarkers to discriminate between NMIBC and MIBC requires further analysis.…”
Section: Exosomal Mirnas In Bladder Cancer Diagnosis and Prognosismentioning
confidence: 99%
“…Urinary biomarkers could also be used to correctly identify MIBC patients that require radical cystectomy, a treatment that severely affects the quality of life. Although no such biomarkers have been identified to date, Baumgart et al identified three miRNAs (miR-30a-3p, miR-99a-5p, and miR-137-3p) that were upregulated and two (miR-141-3p and miR-205-5p) that were downregulated in exosomes secreted by invasive BCa cells versus those secreted by noninvasive BCa cells [ 84 ]. However, the suitability of these miRNAs as liquid biomarkers to discriminate between NMIBC and MIBC requires further analysis.…”
Section: Exosomal Mirnas In Bladder Cancer Diagnosis and Prognosismentioning
confidence: 99%